Banana streak disease survey in three plantain growing regions of Ghana - Lamptey, J.; Dzomeku, B.M.; Anno-Nyako, F.O.; Banful, B.; Hughes, J. (2007)
A banana streak virus disease survey was conducted in 25 districts in 3 of the 6 plantain growing regions of Ghana in 2001. A total of 40 farms were evaluated for the presence of the disease in each region. Triple antibody Sandwich-enzyme-Linked Immunosorbent Assay (ELISA) technique was used in the indexing of the suspected samples. The disease was observed on both land races especially Apantu (False Horn subgroup) and FHIA hybrids on farmers' fields and on research stations. The disease was detected in two of the regions (Ashanti and Brong-Ahafo) studied. The disease was however not detected in the Western region. The disease incidence was observed to be low in all the growing districts studied. The presence of the disease on local cultivars in farmers' fields is a potential threat to the industry.